Conditional Cash Transfers and future poverty reduction: A case study on the Argentinean Asignación Universal por Hijo para Protección Social - Berntsen, Anders (Educação On-line, 2014)
Abstract The article questions the assumption of Conditional Cash Transfer programmes that conditional school attendance – attendance depending on payments – will decrease future poverty. In fact, part of the literature conveys that school attendance should not be the main focus of policies. In the same line of thought, we argue that the priority is not students being at school, but improving the quality of education. Findings from a qualitative fieldwork study on the Argentinean CCT Programme Asignación Universal por Hijo para Protección Social are used to reflect upon this issue. Teachers’ views on the ability of education to help their students out of poverty underline the need of other types of investment, more related to enhancing quality in the Argentinean educational system.